Innovative Modified of Cu-Al/C (C = Biochar, Graphite) Composites for Removal of Procion Red from Aqueous Solution - Alfan Wijaya; Patimah Mega Syah Bahar Nur Siregar; Aldi Priambodo; Neza Rahayu Palapa; Tarmizi Taher; Aldes Lesbani (Science and Technology Indonesia, 2021)
Innovative modification of Cu-Al/C composites was synthesized by coprecipitation method at pH 10 and added biochar (BC) and graphite (GF) to form Cu-Al/BC and Cu-Al/GF composites. Pristine and composites were characterized by XRD, FT-IR, Thermalgravimetric, and surface area using the BET method. The XRD diffraction and FTIR spectrum of Cu-Al/BC and Cu-Al/GF showed that the composite material from LDH, biochar, and graphite was successfully prepared. Modified LDH were surface area higher than the pristine, which obtained 200.90 m2/g and 18.83 m2/g for Cu-Al/BC and Cu-Al/GF respectively.  Cu-Al/BC and Cu-Al/GF were tested for selectivity on several anionic dyes, it was known that procion red (PR) dye was more easily adsorbed than other anionic dyes. Materials were applied as adsorbents of procion red (PR) dye. The advantages of composites were evaluated by the regeneration process of adsorbent on PR. The result of composite toward PR re-adsorption process showed that Cu-Al/BC and Cu-Al/GF had structural stability higher than starting materials until five cycles process. Furthermore, materials were applied as adsorbents of procion red (PR) dye. The maximum adsorption capacity obtained was 93.458 mg/g for Cu-Al/BC and 49.505 mg/g for Cu-Al/GF. Both innovative modified composites have shown effective adsorbents to the removal of PR from an aqueous solution.